SOME ASPECTS OF THE ANALYSIS OF CYCLICAL FLUCTUATIONS IN THE ECONOMY (IN THE CASE OF THE CORONAVIRUS PANDEMIC CRISIS) - Kamoliddin Jabbarov (Соціальна економіка)
The global economy is characterized by cyclical fluctuations, often leading to periods of economic crises. The COVID-19 pandemic, which began in December 2019 in Wuhan, China, has caused a significant economic downturn, exacerbating pre-existing vulnerabilities and introducing new challenges. This paper delves into the intricate dynamics of these cyclical fluctuations, focusing on the recent pandemic crisis and its profound impacts on global economies. It examines the underlying causes and manifestations of economic crises, drawing on historical data and theoretical frameworks from renowned economists such as J.M. Keynes, G. Soros, and contemporary researchers.